Cobalt Catalyzed N‐Methylation of Amides using Methanol. Issue 1 (8th December 2021) - Paul, Bhaskar; Maji, Milan; Panja, Dibyajyoti; Kundu, Sabuj
Abstract: N‐Methylation of amide with methanol is reported in the presence of an in‐situ generated cobalt catalyst. With this simple protocol, various amides were methylated in up to 99% yield. Notably, the involvement of active cobalt (I) hydride in this methylation process was revealed by control experiments. Deuterium labelling studies were carried out using methanol‐d4, taking benzamide and the possible intermediate N‐(hydroxymethyl)benzamide to understand this transformation. Additionally, DFT calculations for the amide−formaldehyde coupling were performed to elucidate the influence of catalyst in this step. Abstract : A cobalt catalyzed N‐methylation of amide using methanol is reported. Control experiments and DFT calculations were performed to realize this catalytic process